Toxicity of entomopathogenic fungal culture filtrate of lowland and highland soil of South Sumatra (Indonesia) against Spodoptera litura larvae - MIMMA GUSTIANINGTYAS; Siti Herlinda; SUWANDI; SUPARMAN; HARMAN HAMIDSON; HASBI; ARUM SETIAWAN; MARIESKA VERAWATY; ELFITA; ARSI (Society for Indonesian Biodiversity, 2020)
Abstract. Gustianingtyas M, Herlinda S, Suwandi, Suparman, Hamidson H, Hasbi, Setiawan A, Verawaty M, Elfita, Arsi. 2020. Toxicity of entomopathogenic fungal culture filtrate of lowland and highland soil of South Sumatra against Spodoptera litura larvae. Biodiversitas 21: 1839-1849. The use of secondary fungal metabolites for the active ingredient of mycoinsecticide is more effective and more easily integrated with other pest control techniques. This study aimed to measure the toxicity of the culture filtrate of entomopathogenic fungi originating from South Sumatra against the Spodoptera litura larvae. Beauveria bassiana (25 isolates) and Metarhizium anisopliae (20 isolates) of South Sumatra were cultured in liquid media and filtered to produce culture filtrate. The larvae which were sick due to the filtrate showed the symptoms of decreased appetite and were not actively moving, while the dead larvae were characterized by being wrinkled, dry, black integument, and odorless. Mortality caused by B. bassiana filtrate was the highest 98% (BJgTs isolate) and not significantly different from the BSwTd2 isolate (94.67%). Yet, the LT50 BSwTd2 isolate was shorter (5.92 days) compared to the LT50 BJgTs isolate (6.35 days). The most toxic M. anisopliae filtrate produced the mortality of 96% (MKbTp2 isolate) and 85.33% (MPdB isolate) each of which had LT50 of 7.36 days and 8.09 days, respectively. So, the most toxic culture filtrate was BSwTd2 isolate of B. bassiana and MKbTp2 isolate of M. anisopliae. The entomopathogenic fungi producing filtrate which are toxic have the potential to be active ingredients of mycoinsecticides.